Community sentiment following the Deepwater Horizon oil spill disaster: A test of time, systemic community, and corrosive community models. (February 2020) - Cope, Michael R.; Slack, Tim; Jackson, Jorden E.; Parks, Vanessa
Abstract: A fundamental concern in the social science scholarship on disasters is understanding community impacts and recovery as a social process. This study examines community sentiment in the aftermath 2010 BP Deepwater Horizon oil spill (DHOS), including the influence of time and the explanatory utility of two major theoretical perspectives—the systemic community model and the corrosive community model—in predicting community sentiment in the context of this disaster. Specifically, our objectives are to assess how community sentiment in the wake of the DHOS: 1) changes over time; 2) is related to the systemic model; and 3) is related to the corrosive model. To meet these objectives, we analyze four waves of data from a unique repeated cross-sectional household survey data—the Louisiana Community Oil Spill Survey (COSS)—collected between 2010 and 2013. Our results demonstrate that 1) accounting for other factors, community sentiment community sentiment was significantly greater in later time periods compared to 2010, and 2) the simultaneous and complimentary utility of the systemic and corrosive community frameworks for understanding community sentiment in the wake of the DHOS. Highlights: We examine the impacts of the 2010 BP-DH disaster on community sentiments. The systemic model of community aids with modeling the disaster social processes. The corrosive community model aids with modeling the disaster social processes. When used together, the systemic and corrosive models are complementary.